Monitoring Energy Efficiency in Buildings with Wireless Sensor Networks: NRG-WiSe Building - Foche, I.; Chidean, M.; Simó-Reigadas, F.J.; Mora-Jiménez, I.; Rojo-Álvarez, J.L.; Ramiro-Bargueno, J.; Caamano, A.J. (IntechOpen, 2012)
None